2008
DOI: 10.1007/s10194-008-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and migraine: a reconsideration of the central theory

Abstract: The 5-hydroxytryptamine (5-HT) has been implicated in migraine pathophysiology for the past 50 years. A low central 5-HT disposition associated with an increase in 5-HT release during attack is the most convincing change of 5-HT metabolism implicated in migraine. Peripheral studies on plasma/platelet have not generally shown low 5-HT levels. Studies on 5-HT reactivity showed hypersensitivity, also expressed as reduced tachyphylaxis (habituation), which successively was evidenced as the most characteristic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 100 publications
(141 reference statements)
3
66
0
2
Order By: Relevance
“…By contrast, during the attack (ie, ictally), habituation and 1st block amplitude increase and normalize, while during the days immediately preceding the attack (ie, preictally), the habituation deficit further worsens. We have postulated that these cortical electrophysiological patterns are related to changes in serotonin transmission, which is low interictally [26], and may further decrease preictally but increase ictally, as suggested by several biochemical studies [27,28] and numerous imaging studies [29,30] showing activation of pontomesencephalic areas comprising monoaminergic nuclei during migraine attacks (see [6] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, during the attack (ie, ictally), habituation and 1st block amplitude increase and normalize, while during the days immediately preceding the attack (ie, preictally), the habituation deficit further worsens. We have postulated that these cortical electrophysiological patterns are related to changes in serotonin transmission, which is low interictally [26], and may further decrease preictally but increase ictally, as suggested by several biochemical studies [27,28] and numerous imaging studies [29,30] showing activation of pontomesencephalic areas comprising monoaminergic nuclei during migraine attacks (see [6] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings numerous studies examined peripheral 5HT and 5HIAA levels in plasma and platelets, and their results suggest that no alteration is present during the migraine attack in 5HT levels compared to controls [102]. These findings are not surprising if we consider that the main source of 5HT and 5HIAA is the gut, where enterochromaffin cells synthesize 5HT to fulfil its role in the modulation of peristalsis [103].…”
Section: Serotonin In Migrainementioning
confidence: 94%
“…Serotonin is a vasoconstrictor [104], and it was revealed that the peripheral veins of migraineurs show higher reactivity to 5HT than controls, furthermore veins of women suffering from migraine react even more to 5HT than veins of migrainous men [102] supporting the involvement of 5HT in migraine.…”
Section: Serotonin In Migrainementioning
confidence: 99%
“…Additionally, this molecule could be found in some plants (Badria, 2002). The fluctuations of platelet and plasma level of 5-hydroxytryptamine (Panconesi, 2008), change in lymphoblastic serotonin level (Nagata et al, 2007) and number of 5-hydroxytryptamine platelet transporters (as indirect index of 5-hydroxytryptamine recovery) (Panconesi, 2008) have been reported in patients with migraine. There are some controversies regarding the role of serotonin in migraine.…”
Section: Serotoninmentioning
confidence: 96%
“…In spite of controversial results about mentioned issues, the importance of the failure of a serotonergic system in migraine pathogenesis is significant. Accordingly, the serotonin system is considered to be involved in migraine (Panconesi, 2008). Moreover, additional studies are necessary to establish its importance in migraine etiology.…”
Section: Serotoninmentioning
confidence: 99%